Sex‐specific incident dementia in patients with central nervous system trauma. Issue 1 (30th April 2019) - Mollayeva, Tatyana; Hurst, Mackenzie; Escobar, Michael; Colantonio, Angela
Abstract: Introduction: Despite evidence that central nervous system (CNS) trauma, including traumatic brain injury and spinal cord injury, can cause sustained neurocognitive impairment, it remains unclear whether trauma‐related variables are associated with incident dementia independently of other known risk factors. Methods: All adults without dementia entering the health‐care system with diagnoses of CNS trauma were examined for occurrence of dementia. All trauma‐related variables were examined as predictors in sex‐specific Cox regression models, controlling for other known risk factors. Results: Over a median follow‐up of 52 months, 32, 834 of 712, 708 patients (4.6%) developed dementia. Traumatic brain injury severity and spinal cord injury interacted with age to influence dementia onset; women were at a greater risk of developing dementia earlier than men, all other factors being equal. Discussion: Risk stratification of patients with CNS trauma by sex is vital in identifying those most likely to develop dementia and in understanding the course and modifying factors.